EVALUASI PERATURAN DAERAH KABUPATEN KAMPAR NOMOR 10 TAHUN 2011 TENTANG PAJAK SARANG BURUNG WALET - Afridona, Zaili Rusli, Febri Yuliani (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Evaluation of Kampar District Regulation Number 10 of 2011 concerning walletbird nest tax. The purpose of this study was to analyze the Evaluation of Kampar RegionalRegulation Number 10 of 2011 concerning Taxes for Swallow's Nest and analyze the factors thatinfluence it. This study uses a qualitative descriptive research method approach. Primary data isobtained directly through interviews with key informants, namely the Head of the Legal Sub-Section of the Kampar Regent's office, the Head of the Kampar District Revenue Service, theRegional Secretary of Kampar Regency in the 2006-2011 period, Entrepreneurs of swiftlet nestbreeding and the communities surrounding swallow nest breeding Secondary data obtained fromresearch documents. The results showed that compliance factors determine the success of theimplementation of the Kampar district regulation Number 10 of 2011 concerning swallow nest tax,but the audit in the form of supervision has not been carried out optimally. Factors affecting theEvaluation of Kampar District Regulation Number 10 of 2011 concerning Taxes for Swallow'sNests include the lack of available human resources who have the competence to carry outevaluations, due to the lack of evaluation culture, uneven quality of human resources, inadequatefacilities, discipline still low, citizen compliance is still low.